Dijo - An Agri-park (agro-processing plant) to empower informal vendors via urban agriculture to alleviate unemployment and food insecurity in Mamelodi West - Hugo, Jan (University of Pretoria, 2020)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2019.